1978
DOI: 10.1210/jcem-47-6-1336
|View full text |Cite
|
Sign up to set email alerts
|

γ-Amino-β-Hydroxy Butyric Acid Stimulates Prolactin and Growth Hormone Release in Normal Women*

Abstract: The influence of gamma-amino-beta-hydroxy butyric acid (GABOB) treatment on pituitary function has been investigated in this study. Different doses (50 x 100 mg) of GABOB were iv injected into three and six normal women, respectively. PRL and GH plasma levels were measured before and after the injection. The treatment with 150 mg GABOB, performed in another two normal women, was interrupted because of side-effects (loss of consciousness etc.) due to the treatment. The treatment with 50 mg GABOB did not induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
1

Year Published

1980
1980
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…As it concerns GH, there are at least five drugs affecting GABAergic mechanisms (y-hydroxybutyric acid, yamino-/Miydroxybutyric acid, muscimol, baclofen, and diazepam) (5,6,(19)(20)(21) that are able to stimulate GH secretion. However, baclofen has been shown to exert opposite effects (decreased GH response to insulin-induced hypoglycemia and arginine) after chronic treatment (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it concerns GH, there are at least five drugs affecting GABAergic mechanisms (y-hydroxybutyric acid, yamino-/Miydroxybutyric acid, muscimol, baclofen, and diazepam) (5,6,(19)(20)(21) that are able to stimulate GH secretion. However, baclofen has been shown to exert opposite effects (decreased GH response to insulin-induced hypoglycemia and arginine) after chronic treatment (22).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for GABAergic control of ACTH, LH, PRL, and GH release has been reported (3)(4)(5)(6). Recently, GABA has been found in a variety of tissues outside of the central nervous system (CNS), with its highest concentration localized in the islets of Langerhans (7,8).…”
mentioning
confidence: 99%
“…Recent studies have clearly shown that GABA-ergic compounds are capable of stimulating growth hor¬ mone secretion Fioretti et al 1978;Takahara et al 1977;Abe et al 1977;Vijayan & McCann 1978a;Tamminga et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, reports on the effects of these com¬ pounds on prolactin release are controversial (In¬ vitti et al 1977;Fioretti et al 1978;Takahara et al 1977;Tamminga et al 1978;Vijayan & McCann 1978b;Mioduszewski et al 1976;Ondo & Pass 1976;Libertun & McCann 1976;Pass & Ondo 1977;Schally et al 1977;Rivier & Vale 1977;Hall et al 1977;Lamberts 8c MacLeod 1978;Locatelliet al 1978). The above investigations were carried out under conditions of acute drug administration and, to our knowledge, no information is at present available on the influence of protracted GABA treatment on growth hormone and prolactin secre¬ tion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation